Osteopathic Manipulative Treatment in Neonatal Intensive Care Units - Luca Cicchitti; Alessandra Di Lelio; Gina Barlafante; Vincenzo Cozzolino; Susanna Di Valerio; Paola Fusilli; Giuseppe Lucisano; Cinzia Renzetti; Marco Verzella; Maria Chiara Rossi (Medical Sciences, 2020)
The aim of this study was to assess the impact of osteopathic manipulative treatment (OMT) on newborn babies admitted at a neonatal intensive care unit (NICU). This was an observational, longitudinal, retrospective study. All consecutive admitted babies were analyzed by treatment (OMT vs. usual care). Treatment group was randomly assigned. Between-group differences in weekly weight change and length of stay (LOS) were evaluated in the overall and preterm populations. Among 1249 babies (48.9% preterm) recorded, 652 received usual care and 597 received OMT. Weight increase was more marked in the OMT group than in the control group (weekly change: +83 g vs. +35 g; p < 0.001). Similar trends were found in the subgroup of preterm babies. A shorter LOS was found in the OMT group vs. the usual care group both in overall population (average mean difference: −7.9 days, p = 0.15) and in preterm babies (−12.3 days; p = 0.04). In severe preterm babies, mean LOS was more than halved as compared to the control group. OMT was associated with a more marked weekly weight increase and, especially in preterm babies, to a relevant LOS reduction: OMT may represent an efficient support to usual care in newborn babies admitted at a NICU.